Normative analysis on school evaluation in Spain in relation to the functions of educational inspection - Estefanía Lera, José Luis (Avances en Supervisión Educativa, 2023)
It is analyzed and commented the interrelationship between the evaluation of schools and the functions of the inspectorate in the Laws on Education in Spain since 1970 and in the regional regulations affecting educational inspection in the different Autonomous Communities. The aim is to draw conclusions that help to highlight the value of both the evaluation of schools and the actions of the inspectorate in this regard, in line with the functions assigned to it by law, which we consider to be of the utmost importance for the quality of the education system, in the current context of educational decentralization and autonomy of the educational centers. We analyze the possible causes of the current lesser importance of the evaluation of schools carried out by the inspectorate, compared to the high importance that this evaluation had in the decade of the nineties of the last century. The paper stresses the need to promote a comprehensive and integrated model of school evaluation that interactively combines external evaluation carried out by the inspectorate with internal evaluation or self-evaluation carried out by the schools, as well as the need for the evaluation function of the educational inspectorate and, specifically, the evaluation of schools, to be one of its priority actions, in accordance with an inspection model focused on evaluation and improvement.